PENYULUHAN KESEHATAN REPRODUKSI SEBAGAI SYARAT PRANIKAH BAGI CALON PENGANTIN; ASPEK POSITIF DAN NEGATIF: - Azzulfa, Fatihatul Anhar (Fakultas Agama Islam UNISMA, 2023)
Health is mostly disregarded in the process of getting married, this is shown by the absence of regulations regarding this matter in both the Marriage Law and KHI, besides that health checks are not mentioned as one of the requirements for marriage in classical fiqh. In some regions, including the Surabaya City, prospective brides and grooms (male/female) are not only required to take a medical check-up, but also to attend reproductive health counseling, in order to frame a harmonious family and produce quality offspring that are free from sexually transmitted diseases. This research aims to explore the positive and negative aspects of the obligation to participate in reproductive health counseling. The method used in this research is qualitative, library research with philosophical and medical approaches, with maqāṣid asy-syarī’ah theory as the analytical tool. The research found that reproductive health counseling for prospective brides has more positive aspects in line with the various maqāṣid asy-syarī’ah, namely ḥifẓ an-nasl, ḥifẓ al-'aql, ḥifẓ an-nafs, ḥifẓ ad-dīn and ḥifẓ al-māl. Kata kunci: Reproductive health, Premarital, Maqāṣid asy-syarī’ah